The human resource :Managing people and work in the 1990 s /Roland Pearson. - Pearson, Roland.
Offers an introduction to the problems of human resource management for undergraduates. The text addresses the issues of change, with particular reference to labour markets and the effective use of people at work, in both public and private organizations. The book also includes case studies